Skrining dan Edukasi Sebagai Upaya Pengendalian Hipertensi - Jamaica, Putri Avanny; Rindarwati, Asti Yunia; Destiani, Dika Pramita; Salsabila, Lyansaputri (Institut Riset dan Publikasi Indonesia (IRPI), 2024)
Hypertension poses significant global challenges and contributes to the rising morbidity and mortality rates associated with cardiovascular diseases, including heart disease and stroke. Commonly referred to as a